Negative pole piece, secondary battery and electric device

By adopting a two-layer structure negative electrode sheet design in lithium-ion batteries, combining porous silicon and graphite materials, the problem of volume expansion and powderization of silicon negative electrode materials during circulation is solved, and the charging capacity and circulation performance of the battery are improved.

CN119230740AActive Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310798399.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The silicon negative electrode material in lithium-ion batteries is powdered and peeled from the current collector due to volume expansion during circulation, resulting in a decrease in charging capacity and cycling performance.

Method used

The negative electrode sheet design adopts a double-layer structure, in which the lower film layer contains less silicon-based negative electrode material to alleviate the powdering problem, the upper film layer contains porous silicon negative electrode material to improve lithium ion embedding capability and kinetics, and passes through porous silicon Combination with graphite and use of carbon nanotubes optimizes the porosity and conductivity of the membrane layer.

Benefits of technology

It effectively improves the energy density and circulation performance of the negative electrode sheet, reduces the problem of surface pores being crushed due to roll pressure, and improves the lithium ion embedding capability and the overall stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230740A_ABST
    Figure CN119230740A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece, a secondary battery and an electric device. The negative pole piece comprises a current collector and a negative pole film layer, and the negative pole film layer comprises a first film layer arranged on one side or two sides of the current collector; the second film layer is arranged on one side, far away from the current collector, of the first film layer; the negative electrode active material in the first film layer and the negative electrode active material in the second film layer respectively and independently comprise a silicon-based negative electrode material, the silicon-based negative electrode material in the second film layer comprises a porous silicon negative electrode material, and the content of the silicon-based negative electrode material in the first film layer is smaller than that of the silicon-based negative electrode material in the second film layer. And the charging capability and the cycle performance of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a negative electrode plate, a secondary battery and an electrical device. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high power density and long cycle life, and are therefore widely used in portable electronic devices such as laptops, mobile phones, digital cameras and other electronic products. In recent years, with the rapid development of new energy and clean energy vehicles, higher requirements have been placed on the performance and safety of new power batteries and energy storage batteries, and the demand for batteries to withstand various extreme working conditions is also growing.

[0003] At present, in order to improve the performance of lithium-ion batteries, many studies are focused on the development and improvement of electrode materials and electrolytes. For example, silicon materials have a higher theoretical specific capacity (>4000mAh / g), which is much higher (about 10 times) than graphite, which is close to the limit capacity, and the voltage to lithium is not high, so it is expected to become the first choice for high energy density batteries. Although the use of silicon anodes to replace part of the traditional graphite anodes can increase the gram capacity of the anode active materials, silicon will produce a dramatic volume expansion during the lithium insertion / extraction process, which makes the silicon material easy to pulverize rapidly during the cycle and fall off the electrode, thereby losing contact with the current collector and failing to give full play to the activity of the silicon material. Summary of the invention

[0004] The present application provides a negative electrode plate, a secondary battery and an electrical device to improve the charging capacity and cycle performance of the secondary battery.

[0005] In a first aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode film layer, the negative electrode film layer comprising: a first film layer, arranged on one side or both sides of the current collector; a second film layer, arranged on a side of the first film layer away from the current collector; the negative electrode active material of the first film layer and the negative electrode active material in the second film layer each independently comprise a silicon-based negative electrode material, and the silicon-based negative electrode material in the second film layer comprises a porous silicon negative electrode material, and the content of the silicon-based negative electrode material in the first film layer is less than the content of the silicon-based negative electrode material in the second film layer.

[0006] In the negative electrode sheet of the present application, the lower first film layer contains silicon-based negative electrode material at the same time, thereby improving the energy density of the negative electrode sheet, and at the same time, the silicon-based negative electrode content in the lower first film layer is relatively small, which effectively alleviates the problem of separation from the current collector caused by pulverization of the silicon-based negative electrode material during the cycle. The second film layer located on the surface has a porous silicon negative electrode material, thereby effectively avoiding the problem of reduced battery gram capacity due to the use of pore-forming agents such as porous carbon; and the porous silicon negative electrode material can increase the surface pores, improve the defect that lithium ions cannot be embedded into the negative electrode of the electrode sheet due to the damage to the surface pores caused by rolling; and the content of silicon-based negative electrode material in the second film layer located on the upper layer is more than that in the first film layer located on the lower layer, especially the upper layer has a porous silicon negative electrode material, so the upper layer preferentially inserts lithium, the lithium insertion path is shorter, and the kinetics are better, thereby improving the charging capacity of the negative electrode sheet, and effectively alleviating lithium precipitation, thereby improving the cycle performance of the battery.

[0007] In any embodiment of the first aspect, the surface density M1 of the first film layer is in the range of 4.5 mg / cm 2 ~20mg / cm 2 The surface density M2 of the second film layer is in the range of 4.5 mg / cm 2 ~20mg / cm 2 .

[0008] In any embodiment of the first aspect, the weight ratio of the first film layer to the second film layer is 95:5 to 30:70, and can further be 90:10 to 40:60, thereby improving the synergistic effect of the two film layers.

[0009] In any embodiment of the first aspect, the porosity of the first film layer ranges from 20% to 50%, the porosity of the second film layer is 20% to 70%, and the porosity of the negative electrode film layer is 20% to 70%, which can not only improve the lithium ion embedding ability, but also increase the gram capacity of the negative electrode sheet.

[0010] In any embodiment of the first aspect, the thickness of the second film layer is 10 μm to 20 μm, which fully solves the problem of the pores on the surface of the negative electrode sheet being crushed due to rolling.

[0011] In any embodiment of the first aspect, the mass content of the silicon-based negative electrode material in the first film layer is 0.5% to 50%; and / or the mass content of the porous silicon negative electrode material in the second film layer is 0.5% to 70%; optionally, the mass content of the porous silicon negative electrode material in the negative electrode film layer is 1% to 60%, so as to utilize the silicon-based negative electrode materials in the two film layers to increase the gram capacity of the negative electrode plate as much as possible.

[0012] In any embodiment of the first aspect, the second film layer comprises a porous silicon negative electrode material, a graphite negative electrode material, a binder, a dispersant and a conductive agent, wherein the conductive agent comprises one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of the porous silicon negative electrode material in the second film layer is 0.5% to 70%; optionally, the mass percentage of the graphite negative electrode material in the second film layer is 25% to 90%; optionally, the mass percentage of the binder in the second film layer is 1% to 8%; optionally, the mass percentage of the dispersant in the second film layer is 0.5% to 2%; optionally, the mass percentage of the conductive carbon in the second film layer is 0.5% to 5%; optionally, the mass percentage of the carbon nanotube in the second film layer is 0.05% to 2%. A porous silicon negative electrode material and a graphite negative electrode material are combined, and the volume stability of the second film layer during the cycle is improved by utilizing the structural stability of the graphite negative electrode material, and the porous silicon negative electrode material is used to improve the gram capacity and lithium ion transmission capacity of the second film layer.

[0013] In any embodiment of the first aspect, the first film layer comprises a silicon-based negative electrode material, a graphite negative electrode material, a binder, a dispersant and a conductive agent, wherein the conductive agent comprises one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of the silicon-based negative electrode material in the first film layer is 0.5% to 50%; optionally, the mass percentage of the graphite negative electrode material in the first film layer is 45% to 97.5%; optionally, the mass percentage of the binder in the first film layer is 1% to 3%; optionally, the mass percentage of the dispersant in the first film layer is 0.3% to 1.5%; optionally, the mass percentage of the conductive carbon in the first film layer is 0 to 3%; optionally, the mass percentage of the carbon nanotube in the first film layer is 0 to 0.5%. The combination of silicon-based negative electrode material and graphite negative electrode material improves the adhesion stability of the first film layer and the current collector, and can improve the gram capacity of the first film layer to a certain extent.

[0014] In any embodiment of the first aspect, the silicon-based negative electrode material of the first film layer includes any one or more of the group consisting of silicon material, silicon oxide material and porous silicon negative electrode material, and the content of the porous silicon negative electrode material in the first film layer is less than the content of the porous silicon negative electrode material in the second film layer, so as to improve the uniformity of the overall pores of the negative electrode film layer.

[0015] In any embodiment of the first aspect, the Dv of the porous silicon negative electrode material 50 The BET specific surface area of ​​the porous silicon negative electrode material is between 1m 2 / g~30m 2 / g; optionally between 6m 2 / g~20m 2 / g. To further improve the volume energy density of the negative electrode.

[0016] In any embodiment of the first aspect, the porous silicon negative electrode material comprises: a core, which is porous silicon, and the porous silicon comprises silicon and silicon compounds, and the silicon compounds comprise silicon oxides; and a coating layer, which is coated on the surface of the core. The porous silicon negative electrode material with a core-shell structure can improve the energy density of the negative electrode sheet while alleviating the volume expansion of the silicon-based negative electrode material, thereby improving the cycle stability of the high energy density battery.

[0017] In any embodiment of the first aspect, the coating layer comprises any one or more of metal compounds of silicon, lithium silicate, amorphous carbon, and carbon nanotubes. By coating the one or more materials, the mechanical structure stability or conductivity of the porous silicon negative electrode material is improved.

[0018] In any embodiment of the first aspect, the coating layer includes: a first coating layer, the first coating layer is coated on the surface of the inner core, and the first coating layer includes lithium silicate; a second coating layer, the second coating layer is coated on the surface of the first coating layer, and the second coating layer includes a metal compound of silicon, and optionally the metal element of the metal compound of silicon includes Ti, Mg and / or Al; a third coating layer, the third coating layer is coated on the surface of the second coating layer, and the third coating layer includes amorphous carbon, and optionally, the material of the amorphous carbon includes hard carbon and / or soft carbon. The first coating layer includes lithium silicate, and lithium salts and inert phases (lithium oxide) can be generated during the lithium insertion process. The generation of lithium salts can reduce the consumption of lithium ions in the positive electrode active material during the first lithium insertion process, so that the battery has a higher first coulomb efficiency. The generation of inert phases can effectively alleviate volume expansion and improve the cycle performance of the battery. The second coating layer arranged between the first coating layer and the third coating layer includes a metal compound of silicon, which has a strong mechanical strength, can buffer the volume expansion of the internal silicon material, and improve the cycle performance. On the one hand, the third coating layer can buffer the volume expansion of the first coating layer and improve the cycle performance; on the other hand, it can improve the protection of the first coating layer, avoid direct contact between the first coating layer and water, and prevent the dissolution and gas generation of lithium silicate in the first coating layer.

[0019] In any embodiment of the first aspect, the silicon compound further comprises a metal compound of silicon, and the metal compound of silicon is coated on the surface of silicon; optionally, the metal element of the metal compound of silicon comprises Ti, Mg and / or Al. Coating the metal compound of silicon on the surface of silicon can buffer the volume expansion of silicon and improve the cycle performance.

[0020] In any embodiment of the first aspect, the coating layer includes: a first coating layer, the first coating layer is coated on the surface of the inner core, and the first coating layer includes lithium silicate; a third coating layer, the third coating layer is coated on the surface of the first coating layer, and the third coating layer includes amorphous carbon. Optionally, the material of the amorphous carbon includes hard carbon and / or soft carbon. The first coating layer includes lithium silicate, which can generate lithium salts and inert phases (lithium oxide) during the lithium insertion process. The generation of lithium salts can reduce the consumption of lithium ions in the positive electrode active material during the first lithium insertion process, so that the battery has a higher first coulomb efficiency. The generation of inert phases can effectively alleviate volume expansion and improve the cycle performance of the battery. On the one hand, the third coating layer can buffer the volume expansion of the first coating layer and improve the cycle performance; on the other hand, it can improve the protection of the first coating layer, avoid direct contact between the first coating layer and water, and prevent the dissolution and gas production of lithium silicate in the first coating layer.

[0021] In any embodiment of the first aspect, the third coating layer further includes carbon nanotubes, which improve the conductivity of the porous silicon negative electrode material, and utilize the carbon nanotubes to fully bind the porous silicon negative electrode material, alleviate the volume expansion during the charge and discharge process, control the polarization inside the negative electrode cell, and improve the cycle performance of the cell.

[0022] In any embodiment of the first aspect, the mass of the porous silicon negative electrode material in the first film layer and the second film layer is m1 and m2 respectively; the mass percentage of the carbon nanotubes in the porous silicon negative electrode material in the first film layer and the second film layer is C1 and C2 respectively; excluding the carbon nanotubes in the porous silicon negative electrode material, the mass of the remaining carbon nanotubes in the first film layer and the second film layer is S1 and S2 respectively, the first film layer and the second film layer are the first film layer per unit area and the second film layer per unit area respectively, and the following relationship is satisfied: (m2×C2+S2) / M2=(m1×C1+S1) / M1, m2≥m1, S1≥S2, S2=m1×m2×(C2-C1) / (m2-m1). By utilizing the restrictions of the above relationship and making full use of the carbon nanotubes, the binding capacity of the silicon-based negative electrode is further improved, the rebound of the negative electrode plate is effectively suppressed, and the polarization of the negative electrode plate is minimized.

[0023] In any embodiment of the first aspect, the Dv50 range of the silicon single substance is: 0<Dv50≤10nm; optionally, the Dv50 range of the silicon single substance is: 2nm<Dv50≤8nm. The use of nano-scale silicon single substance is conducive to the mixing of silicon oxide with it, which is conducive to improving the energy density of the battery, and is conducive to reducing the difficulty of coating the core structure and improving the cycle stability of the battery.

[0024] In any embodiment of the first aspect, the chemical formula of the silicon oxide is SiOx, wherein 0<x≤2; the Dv50 range of the silicon oxide is: 2μm≤Dv50≤13μm, which is conducive to mixing with silicon and improving the energy density of the battery.

[0025] In any embodiment of the first aspect, the lithium silicate comprises one or more of Li2SiO3, Li2Si2O5, Li4SiO4, Li2Si3O7, Li8SiO6, Li6Si2O7, Li4Si2O7, Li2Si4O7 and LiSiO3; optionally, the lithium silicate comprises at least Li2SiO3, and further optionally, the mass of Li2SiO3 is at least 50% of the mass of the first coating layer, and more optionally, the mass of Li2SiO3 is at least 70% of the mass of the first coating layer. The first coating layer effectively reduces the consumption of lithium ions in the positive electrode active material during the first lithium insertion process, so that the battery has a higher first coulombic efficiency.

[0026] In any embodiment of the first aspect, the thickness of the first coating layer is 10% to 80% of the particle radius of the porous silicon negative electrode material, and optionally, the thickness of the second coating layer is 1nm to 50nm; optionally, the thickness of the third coating layer is 1nm to 1000nm, and optionally 5nm to 300nm. Within the above thickness range, the particles can effectively improve the volume expansion of the negative electrode material while improving the energy density of the battery, thereby improving the cycle stability of the high energy density battery.

[0027] The second aspect of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is any of the above negative electrode sheets. The secondary battery of the present application has good charging capacity, high energy density and good cycle performance.

[0028] The third aspect of the present application provides an electric device, comprising a secondary battery, wherein the secondary battery is selected from the secondary batteries mentioned above in the present application. The electric device of the present application has better safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0030] Figure 1 A schematic diagram of the structure of a negative electrode plate provided in one embodiment of the present application.

[0031] Figure 2A schematic diagram of the structure of a porous silicon negative electrode material provided in one embodiment of the present application.

[0032] Figure 3 A schematic diagram of the structure of a porous silicon negative electrode material provided in another embodiment of the present application.

[0033] Figure 4 A schematic structural diagram of a porous silicon negative electrode material provided in yet another embodiment of the present application.

[0034] Figure 5 Schematic diagram of a secondary battery according to one embodiment of the present application.

[0035] Figure 6 yes Figure 5 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0036] Figure 7 is a schematic diagram of a battery module according to an embodiment of the present application.

[0037] Figure 8 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0038] Fig. 9 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0039] Fig.10 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0040] In the drawings, the drawings are not drawn to scale.

[0041] Description of reference numerals:

[0042] 01 current collector; 02 first film layer; 03 second film layer;

[0043] Porous silicon negative electrode material 10; 11 core; 12 first coating layer; 13 second coating layer; 14 third coating layer; 111 silicon element; 112 silicon oxide; 113 silicon metal compound;

[0044] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0045] The following detailed description and drawings of the embodiments of the present application are used to illustrate the principles of the present application, but cannot be used to limit the scope of the present application, that is, the present application is not limited to the described embodiments.

[0046] Below, the embodiments of the negative electrode plate, secondary battery and electric device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0047] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0050] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0051] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0052] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0053] [Secondary battery]

[0054] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can continue to be used by recharging the active materials after the battery is discharged.

[0055] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0056] [Negative electrode]

[0057] In the process of improving the performance of lithium-ion batteries, many studies have gradually found that a reasonable electrode structure design is very important for the ion and electron transport pathways within the entire electrode. By optimizing the electrode structure, the electrode's conductivity and its wettability to the electrolyte can be improved, and the transmission rate of electrons and ions within the entire electrode can be increased, thereby improving the battery's energy density and rate performance. However, it is a great challenge to obtain thick electrodes that have both good electron / ion transport properties and a high loading of active substances.

[0058] For example, even for thick electrode plates with multi-layer coatings, there is still the problem that the surface pores about 10 to 20 μm deep on the surface of the plate are crushed during the rolling process, making it impossible for lithium ions in the electrolyte to effectively diffuse into the interior of the plate, resulting in a significant reduction in charging capacity. In order to solve this problem, there is a technology that increases the surface porosity by adding pore-forming agents to the surface film layer of the negative electrode plate, such as using porous carbon. However, the use of porous carbon leads to a loss in the energy density of the plate, thereby reducing the gram capacity of the battery. In order to solve the above problems, a typical embodiment of the present application provides a negative electrode plate, such as Figure 1 As shown, the negative electrode plate includes a current collector 01 and a negative electrode film layer, the negative electrode film layer includes a first film layer 02 and a second film layer 033, the first film layer 02 is arranged on one side or both sides of the current collector 01; the second film layer 03 is arranged on the side of the first film layer 02 away from the current collector 01; the negative electrode active material of the first film layer 02 and the negative electrode active material in the second film layer 03 each independently include a silicon-based negative electrode material, and the silicon-based negative electrode material in the second film layer 03 includes a porous silicon negative electrode material 10, and the content of the silicon-based negative electrode material in the first film layer 02 is less than the content of the silicon-based negative electrode material in the second film layer 03.

[0059] In the negative electrode sheet of the present application, the lower first film layer 02 also contains silicon-based negative electrode materials, thereby improving the energy density of the negative electrode sheet. At the same time, the silicon-based negative electrode content in the lower first film layer 02 is relatively small, which effectively alleviates the problem of pulverization of the silicon-based negative electrode material during the cycle and peeling off from the current collector 01. The second film layer 03 located on the surface has a porous silicon negative electrode material 10, thereby effectively avoiding the problem of reduced battery gram capacity due to the use of pore-forming agents such as porous carbon; and the porous silicon negative electrode material 10 can increase the surface pores and improve the defect that lithium ions cannot be embedded in the negative electrode of the electrode sheet due to the damage to the surface pores caused by rolling; and the content of silicon-based negative electrode material in the second film layer 03 located on the upper layer is more than that in the first film layer 02 located on the lower layer, especially the upper layer has a porous silicon negative electrode material 10, so the upper layer preferentially inserts lithium, the lithium insertion path is shorter, and the kinetics are better, thereby improving the charging capacity of the negative electrode sheet, and effectively alleviating lithium precipitation, thereby improving the cycle performance of the battery.

[0060] The above-mentioned first film layer 02 can be directly contacted and arranged on the current collector 01, or a primer layer can be arranged between the first film layer 02 and the current collector 01; the above-mentioned second film layer 03 can be directly contacted and arranged on the first film layer 02, or other negative electrode film layers can be arranged between the two, as long as the second film layer 03 is located on the surface of the negative electrode plate.

[0061] The content of the above silicon-based negative electrode material can be determined by referring to the following method: the first step is to prepare a plurality of negative electrode sheet samples with different mass ratios, which are obtained by mixing silicon-based negative electrode material and graphite material (if there are other negative electrode materials in the negative electrode sheet to be measured, the negative electrode sheet samples can be prepared with reference to the material type of the negative electrode sheet to be measured); the second step is to take samples respectively, place them in a scanning electron microscope for energy spectrum test, and obtain the relative mass percentage of silicon element in each negative electrode sheet sample; the third step is to use the relative mass percentage of silicon element in each negative electrode sheet sample to obtain the relative mass percentage of silicon element in each negative electrode sheet sample. The standard curve is drawn with the mass percentage of silicon-based negative electrode material in each negative electrode sheet sample as the horizontal axis and the mass percentage of silicon-based negative electrode material in each negative electrode sheet sample as the vertical axis to obtain a quantitative relationship. In the fourth step, for the negative electrode sheet to be tested, the thickness of the upper and lower film layers is confirmed by CP (ion beam) sectioning, and then the powder scraping method is used to scrape out the powder of the upper second film layer, and then the powder of the lower first film layer is scraped out, and the relative mass percentage of silicon element is measured, and then the mass percentage of silicon-based negative electrode material in the first and second film layers to be tested is calculated according to the quantitative relationship.

[0062] In some embodiments, the surface density M1 of the first film layer 02 is in the range of 4.5 mg / cm 2 ~20mg / cm 2 The surface density M2 of the second film layer 03 is in the range of 0.2 mg / cm 2 ~20mg / cm 2 The above weight range ensures the effective thickness of the two film layers. In some embodiments, the surface density M1 of the first film layer 02 can be 4.5 mg / cm 2 , 5mg / cm 22 , 7mg / cm 2 、10mg / cm 2 、15mg / cm 2 and 20mg / cm 2 , preferably 5 mg / cm 2 ~7mg / cm 2 In some embodiments, the surface density M2 of the second film layer 03 may be 0.2 mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 5mg / cm 2 、10mg / cm 2 、17mg / cm 2 and 20mg / cm 2 , preferably 0.3 mg / cm 2 ~17mg / cm2 .

[0063] The main function of the second film layer 03 of the present application is to utilize the porous silicon negative electrode material 10 therein to increase the surface porosity. In some embodiments, the weight ratio of the first film layer 02 and the second film layer 03 is 95:5-30:70, and can be further optionally 90:10-40:60, such as 90:10, 80:20, 70:30, 60:40, 50:50 or 40:60. In the above embodiments, especially when the first film layer 02 is used as the main body of the negative electrode film layer, the main function of the negative electrode plate is played, and the second film layer 03 is used to compensate for the defects of the first film layer 02, thereby improving the synergistic effect of the two film layers.

[0064] In some embodiments, the porosity of the first film layer 02 is in the range of 20% to 50%, the porosity of the second film layer 03 is in the range of 20% to 70%, and the porosity of the negative electrode film layer is in the range of 20% to 70%, for example, 20%, 30%, 40%, 50%, 60% or 70%. The negative electrode film layer having the above porosity can utilize the pores to improve the lithium ion embedding ability, and can also utilize the negative electrode active material to improve the gram capacity of the negative electrode sheet.

[0065] In some embodiments, the thickness of the second film layer 03 is 10 μm to 20 μm, such as 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, which fully solves the problem of the pores on the surface of the negative electrode sheet being crushed due to rolling.

[0066] The method for determining the weight of the above two film layers can refer to the following process: confirm the thickness of the upper and lower film layers through the CP section, and then use the powder scraping method to first scrape out the powder of the upper second film layer and weigh it; then scrape out the powder of the lower first film layer and weigh it, and you can get the weight and ratio of the first film layer and the second film layer respectively.

[0067] The method for determining the above porosity can be referred to as follows: take a photo of the CP section, scan it with imaging software, calculate the porosity of the corresponding section and the first film layer 02 and the second film layer 03, then scan and take photos of multiple CP sections, and calculate with software to obtain the porosity of the first film layer 02 and the second film layer 03 in the electrode.

[0068] In order to increase the energy density of the negative electrode plate as much as possible, in some embodiments, the mass content of the silicon-based negative electrode material in the first film layer 02 is 0.5% to 50%, which can be 1% to 45%, 1% to 15%, 2% to 10% or 5% to 10%, such as 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%; and / or the mass content of the porous silicon negative electrode material 10 in the second film layer 03 is 0.5% to 70%, which can be 5% to 65%, 10% to 60%, 10% to 15%, 2% to 10% or 5% to 10%. 5% to 55% or 20% to 50%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%; Optionally, the mass content of the porous silicon negative electrode material 10 in the negative electrode film layer is 1% to 60%, which can be 5% to 55%, 5% to 25%, 5% to 20% or 10% to 20%, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%. The silicon-based negative electrode material in the two film layers is used to increase the gram capacity of the negative electrode plate as much as possible.

[0069] In some embodiments, in addition to silicon-based negative electrode materials, the negative electrode active material may also use negative electrode active materials for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, lithium titanate, etc. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0070] In addition to containing negative electrode active materials, the first film layer and the second film layer of the present application also contain binders, dispersants and conductive agents contained in conventional negative electrode film layers. In some embodiments, the above-mentioned second film layer includes porous silicon negative electrode material, graphite negative electrode material, binder, dispersant and conductive agent, and the conductive agent includes one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of porous silicon negative electrode material in the second film layer is 0.5% to 70%; optionally, the mass percentage of graphite negative electrode material in the second film layer is 25% to 90%; optionally, the mass percentage of binder in the second film layer is 1% to 8%; optionally, the mass percentage of dispersant in the second film layer is 0.5% to 2%; optionally, the mass percentage of conductive carbon in the second film layer is 0.5% to 5%; optionally, the mass percentage of carbon nanotubes in the second film layer is 0.05% to 2%. A combination of porous silicon negative electrode material and graphite negative electrode material is used, the structural stability of the graphite negative electrode material is used to improve the volume stability of the second membrane layer during the cycle, and the porous silicon negative electrode material is used to improve the gram capacity and lithium ion transmission capacity of the second membrane layer.

[0071] In some embodiments, as an example, the binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0072] In some embodiments, as examples, the conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0073] In some embodiments, as examples, the dispersant includes at least one of sodium carboxymethylcellulose (CMC), polyvinylpyrrolidone (PVP), and polyacrylamide (PAM).

[0074] In some embodiments, the first film layer comprises a silicon-based negative electrode material, a graphite negative electrode material, a binder, a dispersant and a conductive agent, wherein the conductive agent comprises one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of the silicon-based negative electrode material in the first film layer is 0.5% to 50%; optionally, the mass percentage of the graphite negative electrode material in the first film layer is 45% to 97.5%; optionally, the mass percentage of the binder in the first film layer is 1% to 3%; optionally, the mass percentage of the dispersant in the first film layer is 0.3% to 1.5%; optionally, the mass percentage of the conductive carbon in the first film layer is 0 to 3%; optionally, the mass percentage of the carbon nanotube in the first film layer is 0 to 0.5%. The content of the graphite negative electrode material in the first film layer is higher than that of the graphite negative electrode material in the second film layer, thereby improving the structural stability of the first film layer and the adhesion stability of the current collector; and the addition of the silicon-based negative electrode material can increase the gram capacity of the first film layer to a certain extent.

[0075] In addition, the carbon nanotubes in the conductive agent in the first film layer and the second film layer have better conductivity, and the linear structure of the carbon nanotubes can restrain the silicon-based negative electrode material to a certain extent, effectively alleviating the volume expansion of the silicon-based negative electrode material, reducing its pulverization, and thus improving the cycle performance of the battery.

[0076] In some arbitrary embodiments, the silicon-based negative electrode material of the first film layer includes any one or more of the group consisting of silicon material, silicon oxide material and porous silicon negative electrode material, or the silicon-based negative electrode material of the first film layer is a porous silicon negative electrode material, as long as the content of the porous silicon negative electrode material in the first film layer is less than the content of the porous silicon negative electrode material in the second film layer, so as to improve the uniformity of the overall pores of the negative electrode film layer.

[0077] In some embodiments, the Dv of the porous silicon negative electrode material 50 The BET specific surface area of ​​the porous silicon negative electrode material is between 1 and 30 m 2 / g; optionally between 6m 2 / g~20m 2 / g. To further improve the cycle performance and charging capacity of the negative electrode.

[0078] The above Dv50 can be measured with reference to the standard GB / T 19077.1-2016 using a laser particle size analyzer (such as MalvernMaster Size 3000). Wherein, Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the measured material reaches 50%.

[0079] The BET specific surface area is the specific surface area of ​​a material measured using a low temperature nitrogen adsorption-desorption method.

[0080] Material porosity: The porosity of silicon-based negative electrode materials can be tested by a true density porosity tester (such as AccuPycⅡ1340).

[0081] The porous silicon negative electrode material of the present application can be a commonly used porous silicon negative electrode material in the art, such as a simple porous silicon material or a coated porous silicon material. In some embodiments, Figures 2 to 4 As shown in any example, the porous silicon negative electrode material includes a core 11 and a coating layer, wherein the core 11 is porous silicon, and the porous silicon includes silicon element 111 and silicon compounds, and the silicon compounds include silicon oxide 112; the coating layer is coated on the surface of the core. The porous silicon negative electrode material with a core-shell structure can improve the charging capacity of the negative electrode plate while alleviating the volume expansion of the silicon-based negative electrode material, thereby improving the cycle stability of the high energy density battery. Those skilled in the art can obtain the composition of the porous silicon in the core of the porous silicon material by excluding the substances in the external coating layer through nuclear magnetic resonance NMR technology (such as equipment BRUKERAVANCEⅢHD 500MHz).

[0082] "Silicon" has a high theoretical lithium insertion capacity (about 4200mAh / g) and a low lithium insertion potential, and has great application potential in the battery field, but the volume expansion effect of silicon is large, resulting in poor battery cycle stability. "Silicon oxide" refers to a binary compound composed of silicon and oxygen. The volume expansion effect of silicon oxide is smaller than that of silicon. Compared with silicon, silicon oxide can alleviate the volume expansion effect and improve the cycle stability of the battery.

[0083] In some embodiments, the coating layer includes any one or more of a metal compound of silicon, lithium silicate, amorphous carbon, and carbon nanotubes. By coating the one or more materials, the mechanical structure stability or conductivity of the porous silicon negative electrode material is improved. There may be a variety of coating methods for the above materials, which may be a single-layer coating if feasible, or the materials may be coated in a multi-layer coating method.

[0084] "Lithium silicate" refers to a series of compounds produced by the reaction of metallic lithium and silicic acid; "amorphous carbon" refers to a transition state of carbon, which is an allotrope of carbon, and usually refers to carbon elements other than graphite and diamond.

[0085] like Figure 2As shown, in some embodiments, the coating layer includes a first coating layer 12 and a third coating layer 14. The first coating layer 12 is coated on the surface of the core 11, and the first coating layer 12 includes lithium silicate; the third coating layer 14 is coated on the surface of the first coating layer 12, and the third coating layer 14 includes amorphous carbon. Optionally, the material of the amorphous carbon includes hard carbon and / or soft carbon. The first coating layer includes lithium silicate, which can generate lithium salts and inert phases (lithium oxide) during the lithium insertion process. The generation of lithium salts can reduce the consumption of lithium ions in the positive electrode active material during the first lithium insertion process, so that the battery has a higher first coulomb efficiency and charging capacity. The generation of inert phases can effectively alleviate volume expansion and improve the cycle performance of the battery. On the one hand, the third coating layer can buffer the volume expansion of the first coating layer and improve the cycle performance; on the other hand, it can improve the protection of the first coating layer, avoid direct contact between the first coating layer and water, and prevent the dissolution and gas generation of lithium silicate in the first coating layer.

[0086] Figure 2 The porous silicon negative electrode material shown can be prepared by the following method:

[0087] 1. Silicon grains and silicon dioxide are prepared by vapor deposition to obtain silicon oxide. The D of silicon oxide is adjusted by adjusting the vapor deposition temperature between 600℃ and 1200℃. V 50. Disperse silicon dioxide particles in water, then add polyvinyl pyrrolidone (molar ratio to silicon dioxide is 5 to 15:1), heat to boil and reflux for 2h to 5h, cool to room temperature, add inorganic alkali solution (concentration is 0.01mmol / L to 0.1mmol / L, such as sodium hydroxide solution), stir and etch for several hours, centrifuge the obtained suspension, wash it with water 2-3 times, dry it at 100℃ to 110℃ for 1h to 3h, and then calcine it in a muffle furnace at 500℃ to 600℃ for 3h to 5h, and porous silicon dioxide can be obtained as the core structure. By grinding the porous silicon dioxide, its D V 50 distribution, for example, adjusting the grinding time between 0.5h and 24h to make D V 50 changes, and further D V 50 for further adjustments;

[0088] 2. Amorphous carbon: After mixing an amorphous carbon source such as asphalt with the above core structure, the mixture is subjected to high temperature treatment for 1 h to 10 h (for example, the amorphous carbon source and the core structure are mixed in a mass ratio of 0.01:1 to 0.1:1), and the temperature is controlled at 700° C. to 1500° C. to obtain a coating layer containing amorphous carbon;

[0089] 3. Mix the material obtained in the above step 2 with a lithium source (for example, the material obtained in step 2 is mixed with the lithium source in a mass ratio of 1:0.09 to 1:0.2), such as lithium powder, lithium hydride, lithium oxide, lithium carbonate or organic lithium, and treat at a high temperature of 300° C. to 1000° C. for 1 h to 5 h. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate coated on the core structure is formed inside the amorphous carbon;

[0090] 4. Finally, the material obtained in step 3 is mixed with the solution of carbon nanotubes, wherein the mass ratio of the material obtained in step 3 to the carbon nanotubes is 1:0.02 to 1:0.1, and a bonding reaction occurs under high temperature treatment at 100°C to 400°C to coat the carbon nanotubes on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0091] like Figure 3 As shown, in some embodiments, the coating layer includes a first coating layer 12, a second coating layer 13 and a third coating layer 14. The first coating layer 12 is coated on the surface of the core 11, and the first coating layer 12 includes lithium silicate; the second coating layer 13 is coated on the surface of the first coating layer 12, and the second coating layer 13 includes a metal compound of silicon, and optionally the metal element of the metal compound of silicon includes Ti, Mg and / or Al; the third coating layer 14 is coated on the surface of the second coating layer 13, and the third coating layer 14 includes amorphous carbon, and optionally the material of the amorphous carbon includes hard carbon and / or soft carbon. The second coating layer further disposed between the first coating layer and the third coating layer includes a metal compound of silicon, which has a strong mechanical strength, can buffer the volume expansion of the internal silicon material, and improve the cycle performance.

[0092] Figure 3 The porous silicon negative electrode material shown can be prepared by the following method:

[0093] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon oxide. The silicon oxide particles are dispersed in water, and then polyvinyl pyrrolidone (with a molar ratio of 5 to 15:1 to silicon dioxide) is added, heated to boiling reflux for 2h to 5h, and then an inorganic alkali solution (with a concentration of 0.01mmol / L to 0.1mmol / L, such as sodium hydroxide solution) is added after cooling to room temperature, and then stirred and etched for several hours. The obtained suspension is centrifuged, washed with water 2-3 times, dried at 100℃ to 110℃ for 1h to 3h, and then calcined in a muffle furnace at 500℃ to 600℃ for 3h to 5h to obtain porous silicon oxide as a core structure;

[0094] 2. Amorphous carbon: Mix an amorphous carbon source such as asphalt with the above core structure and then perform high temperature treatment for 1h to 10h at a temperature of 700°C to 1500°C to obtain a coating layer containing amorphous carbon;

[0095] 3. The material obtained in step 2 is mixed with a lithium source, such as lithium powder, lithium hydride, lithium oxide, lithium carbonate or organic lithium, and subjected to high temperature treatment at 300°C to 1000°C for 1h to 5h. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate is formed inside the amorphous carbon and coated on the core structure;

[0096] 4. Preparation of a metal compound coating layer of silicon: the metal coating raw material is mixed with the material obtained in step 3 at a mass ratio of 0.001:1 to 0.02:1, the mixed material is subjected to a high temperature treatment at 600°C to 1000°C for 0.5h to 2h, the treated material is subjected to ball milling stirring for 10min to 60min, the metal ions will pass through the amorphous carbon coating layer, and a second coating layer of a metal compound containing silicon is formed inside the amorphous carbon and on the surface of the lithium silicate;

[0097] 5. Finally, the material obtained in step 4 is mixed with the solution of carbon nanotubes, and subjected to high temperature treatment at 100° C. to 400° C. to cause a bonding reaction, so that the carbon nanotubes are coated on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0098] The above-mentioned metal coating raw materials include but are not limited to metal salts and metal oxides.

[0099] like Figure 4 As shown, in some embodiments, Figure 2 Based on the structure shown, the silicon compound further includes a silicon metal compound 113, and the silicon metal compound 113 is coated on the surface of the silicon element. "Silicon metal compound" refers to a compound formed by transition metal and silicon; optionally, the metal element of the silicon metal compound includes Ti, Mg and / or Al. Coating the silicon metal compound on the surface of the silicon element can buffer the volume expansion of the silicon element and improve the cycle performance and charging capacity.

[0100] Figure 4 The porous silicon negative electrode material shown can be prepared by the following method:

[0101] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon oxide. The silicon oxide particles are dispersed in water, and then polyvinyl pyrrolidone (with a molar ratio of 5 to 15:1 to silicon dioxide) is added, heated to boiling reflux for 2h to 5h, and then an inorganic alkali solution (with a concentration of 0.01mmol / L to 0.1mmol / L, such as sodium hydroxide solution) is added after cooling to room temperature, and then stirred and etched for several hours. The obtained suspension is centrifuged, washed with water 2-3 times, dried at 100℃ to 110℃ for 1h to 3h, and then calcined in a muffle furnace at 500℃ to 600℃ for 3h to 5h to obtain porous silicon oxide;

[0102] 2. Preparation of metal compound coating layer of silicon: the metal coating raw material is mixed with the porous silicon oxide, the mixed material is subjected to high temperature treatment at 800°C to 1300°C for 1h to 6h, and the high temperature treated material is ground, the coating directly reacts with the silicon grains through phase selective reaction, and a metal compound coating layer of silicon is formed on the surface of the silicon single substance as a core structure;

[0103] 3. Amorphous carbon: Mix an amorphous carbon source such as asphalt with the above core structure and then perform high temperature treatment for 1h to 10h, with the temperature controlled at 700°C to 1500°C to obtain a coating layer containing amorphous carbon;

[0104] 4. The material obtained in step 3 is mixed with a lithium source, such as lithium powder, lithium hydride, lithium oxide, lithium carbonate or organic lithium, and subjected to high temperature treatment at 300° C. to 1000° C. for 1 h to 5 h. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate is formed inside the amorphous carbon and coated on the core structure;

[0105] 5. Finally, the material obtained in step 4 is mixed with the solution of carbon nanotubes, and subjected to high temperature treatment at 100° C. to 400° C. to cause a bonding reaction, so that the carbon nanotubes are coated on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0106] The above-mentioned hard carbon refers to carbon that is difficult to graphitize, and is a thermal decomposition product of high molecular polymers. Common hard carbons include resin carbon, organic polymer pyrolysis carbon and carbon black. Soft carbon generally refers to black carbon, which is a type of highly aromatic substance produced by pyrolysis and carbonization of fossil fuels and biomass under anaerobic conditions. In the above-mentioned embodiments of the present application, amorphous carbon may be only hard carbon, or only soft carbon, or a mixture of hard carbon and soft carbon. Due to the large interlayer spacing and fast lithium insertion rate of amorphous carbon, it is beneficial to improve the overall performance of the battery.

[0107] In some embodiments, the third coating layer further includes carbon nanotubes. Carbon nanotubes can improve the conductivity of porous silicon negative electrode materials, and carbon nanotubes can be used to fully bind porous silicon negative electrode materials, alleviate volume expansion during charging and discharging, control the polarization inside the negative electrode cell, and improve the cycle performance of the cell. Definition: The mass of the porous silicon negative electrode material 10 in the first film layer 02 and the second film layer 03 are m1 and m2 respectively; the mass percentage of carbon nanotubes belonging to the porous silicon negative electrode material 10 in the first film layer 02 and the second film layer 03 are C1 and C2 respectively; excluding the carbon nanotubes in the porous silicon negative electrode material 10, the mass of the remaining carbon nanotubes in the first film layer 02 and the second film layer 03 are S1 and S2 respectively, and the first film layer 02 and the second film layer 03 are the first film layer 02 per unit area and the second film layer 03 per unit area respectively. In order to ensure sufficient binding of the porous silicon negative electrode material 10 and effectively suppress the rebound of the negative electrode pole piece, in some embodiments, the carbon nanotubes in the third coating layer, the carbon nanotubes in the first film layer 02, and the carbon nanotubes in the second film layer 03 are designed to satisfy the following relationship: (m2×C2+S2) / M2=(m1×C1+S1) / M1, m2≥m1, S1≥S2, S2=m1×m2×(C2-C1) / (m2-m1), which further improves the binding ability of the silicon-based negative electrode, effectively suppresses the rebound of the negative electrode pole piece, and minimizes the polarization of the negative electrode pole piece.

[0108] The masses of the porous silicon negative electrode materials in the first film layer and the second film layer are respectively m1 and m2, and the determination method of the content of the silicon-based negative electrode material is referred to.

[0109] Determination of the mass percentage C1 and C2 of the carbon nanotubes on the surface of the above-mentioned porous silicon negative electrode material: SEM can be used to count the number and length of carbon nanotubes on the surface of multiple silicon particles, and the mass of the corresponding single carbon nanotube is obtained by simulating the chain length and molecular number of the carbon nanotubes. The average value is obtained by calculating the number of multiple carbon tubes as the mass of the carbon nanotubes on the surface of the porous silicon negative electrode material, and then the mass percentage C1 and C2 of the carbon nanotubes in the porous silicon negative electrode material are calculated through the volume and true density of the porous silicon negative electrode material.

[0110] The masses of the remaining carbon nanotubes in the first film layer and the second film layer are S1 and S2 respectively: the thickness of the upper and lower film layers is confirmed by CP (ion beam) sectioning, and then the powder of the upper second film layer is scraped out by the powder scraping method, and then the powder of the lower first film layer is scraped out, and then each is divided into n parts of equal mass to ensure uniform distribution on the SEM sample stage, and then the number of carbon nanotubes is counted through SEM testing, and the mass of the carbon nanotubes in the first film layer and the second film layer is calculated using the calculation method in the above method.

[0111] In some embodiments, the Dv50 range of the silicon single substance is: 0<Dv50≤10nm; optionally, the Dv50 range of the silicon single substance is: 2nm<Dv50≤8nm. The use of nano-scale silicon single substance is conducive to the mixing of silicon oxide with it, thereby improving the charging capacity of the battery; and it is conducive to reducing the difficulty of coating the core structure and improving the cycle stability of the battery.

[0112] The chemical formula of "silicon oxide" is SiOx, where 0 < x ≤ 2, such as silicon monoxide (SiO) and silicon dioxide (SiO2). In some embodiments, the Dv50 range of the silicon oxide used is: 2 μm ≤ Dv50 ≤ 13 μm. This is conducive to mixing with silicon and improving the energy density of the battery.

[0113] In some embodiments, the lithium silicate includes one or more of Li2SiO3, Li2Si2O5, Li4SiO4, Li2Si3O7, Li8SiO6, Li6Si2O7, Li4Si2O7, Li2Si4O7 and LiSiO3; optionally, the lithium silicate includes at least Li2SiO3, so that the first coating layer effectively reduces the consumption of lithium ions in the positive electrode active material during the first lithium insertion process, so that the battery has a higher first coulomb efficiency. Further optionally, the mass of Li2SiO3 is at least 50% of the mass of the first coating layer, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, and more optionally, the mass of Li2SiO3 is at least 70% of the mass of the first coating layer, to ensure the higher lithium conductivity of the first coating layer and improve the charging capacity of the overall material.

[0114] According to the type of lithium silicate in the first coating layer, standard samples with different Li2SiO3 contents were prepared, and the test contents of different Li2SiO3 contents were obtained by TOF-SIMES testing, and a standard curve of test content and actual content was established. The test content of Li2SiO3 was obtained by TOF-SIMES testing the first coating layer, and the accurate content of Li2SiO3 was obtained by comparing with the standard curve.

[0115] In any embodiment of the first aspect, the thickness of the first coating layer is 10% to 80% of the particle radius of the porous silicon negative electrode material. Optionally, the thickness of the second coating layer is 1nm to 50nm; optionally, the thickness of the third coating layer is 1nm to 1000nm, optionally 5nm to 300nm. Within the above thickness range, the particles effectively improve the volume expansion of the negative electrode material while improving the battery energy density, and improve the cycle stability and charging capacity of the high energy density battery. The above thickness is tested from the outside to the inside of the particle by TOF-SIMES, and the thickness of each coating layer is judged by the material at different depths. When preparing porous silicon negative electrode materials, the amount of raw materials corresponding to each coating layer is adjusted to adjust its thickness.

[0116] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0117] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0118] [Positive electrode]

[0119] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0120] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0123] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0124] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0125] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0126] [Electrolytes]

[0127] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0128] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0129] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0130] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0131] In some embodiments, the electrolyte may further include additives. As examples, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0132] [Isolation film]

[0133] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0134] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0135] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0136] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0137] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0138] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.

[0139] In some embodiments, reference Figure 6, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0140] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0141] Figure 7 4 is an example of a battery module. Figure 7 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0142] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0143] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0144] Figure 8 and Fig. 9 1 is a battery pack 1 as an example. Figure 8 and Fig. 9 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0145] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0146] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0147] Fig.10 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0148] [Example]

[0149] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0150]

[0151] 1. Porous silicon negative electrode material

[0152] Preparation process of porous silicon negative electrode material 1

[0153] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon oxide, wherein the deposition temperature is controlled to be 800°C, silicon oxide particles are dispersed in water, and then polyvinyl pyrrolidone (with a molar ratio of 10:1 to silicon dioxide) is added, heated to boiling reflux for 3 hours, and then a sodium hydroxide solution with a concentration of 0.05 mmol / L is added after cooling to room temperature, and then stirred and etched for 4 hours. The obtained suspension is washed with water 2-3 times after centrifugation, dried at 105°C for 2 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain porous silicon oxide. The obtained porous silicon oxide is ground and sieved, and its D V 50 size;

[0154] 2. Preparation of metal compound coating layer of silicon: The metal coating raw material TiO2 and the silicon oxide are mixed at a mass ratio of 0.003:1, the mixed material is subjected to high temperature treatment at 1000°C for 4 hours, and the high temperature treated material is ground. The coating directly reacts with the silicon grains through a phase selective reaction to obtain a silicon TiSi coating layer formed on the surface of the silicon single substance as a core structure;

[0155] 3. Amorphous carbon: The asphalt and the core structure are mixed at a mass ratio of 0.05:1 and then subjected to high temperature treatment for 6 hours at a temperature controlled at 1100°C to obtain a coating layer containing amorphous carbon;

[0156] 4. The material obtained in the above step 3 is mixed with lithium carbonate in a mass ratio of 1:0.2, and subjected to high temperature treatment at 800° C. for 3 h, so that the lithium ions pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate coated on the core structure is formed inside the amorphous carbon;

[0157] 5. Finally, the material obtained in step 4 is mixed with the solution of carbon nanotubes, wherein the mass ratio of the material obtained in step 4 to the carbon nanotubes is 1:0.08, and a bonding reaction occurs under high temperature treatment at 250°C to coat the carbon nanotubes on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0158] Based on the preparation process of the porous silicon negative electrode material 1, the porous silicon negative electrode materials 2 to 5 are obtained by adjusting the grinding time and the sieving particle size.

[0159] Based on the preparation process of the porous silicon negative electrode material 1, porous silicon negative electrode materials 6 to 10 are obtained by adjusting the temperature of vapor deposition.

[0160] On the basis of the above-mentioned preparation process of the porous silicon negative electrode material 1 , the mass contents of the porous silicon material and lithium carbonate are adjusted to obtain porous silicon negative electrode materials 11 to 14 with different first coating layer thicknesses.

[0161] Based on the above-mentioned preparation process of the porous silicon negative electrode material 1, the amount of the metal coating raw material TiO2 is halved to obtain the porous silicon negative electrode material 15.

[0162] Preparation process of porous silicon negative electrode material 16

[0163] The only difference from the preparation process of the porous silicon negative electrode material 1 is that MgCl2 is used to replace TiO2.

[0164] Preparation process of porous silicon negative electrode material 17

[0165] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon oxide, wherein the deposition temperature is controlled to be 800°C, silicon oxide particles are dispersed in water, and then polyvinyl pyrrolidone (with a molar ratio of 10:1 to silicon dioxide) is added, heated to boiling reflux for 3 hours, and then sodium hydroxide solution is added after cooling to room temperature, and then stirred and etched for several hours. The obtained suspension is centrifuged, washed with water 2-3 times, dried at 105°C for 2 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain porous silicon oxide as a core structure. The obtained porous silicon oxide is ground and sieved to adjust its D V 50 size;

[0166] 2. Amorphous carbon: The asphalt and the core structure are mixed at a mass ratio of 0.05:1 and then subjected to high temperature treatment for 6 hours at a temperature controlled at 1000°C to obtain a coating layer containing amorphous carbon;

[0167] 3. The material obtained in step 2 is mixed with lithium carbonate in a mass ratio of 1:1.2, and treated at 800°C for 3 hours. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate is formed inside the amorphous carbon and coated on the core structure;

[0168] 4. Preparation of metal compound coating layer of silicon: the metal coating raw material is mixed with the material obtained in step 3 at a mass ratio of 0.015:1, the mixed material is subjected to high temperature treatment at 1000°C for 1 hour, the treated material is subjected to ball milling stirring, and stirring for 30 minutes, the metal ions will pass through the amorphous carbon coating layer, and a second coating layer of metal compound containing silicon is formed inside the amorphous carbon and on the surface of lithium silicate;

[0169] 5. Finally, the material obtained in step 4 is mixed with the solution of carbon nanotubes, wherein the mass ratio of the material obtained in step 4 to the carbon nanotubes is 1:0.08, and a bonding reaction occurs at a high temperature of 250° C., and the carbon nanotubes are coated on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0170] Based on the preparation process of the porous silicon negative electrode material 17, porous silicon negative electrode materials 18 to 21 are obtained by adjusting the amount of the metal coating raw material.

[0171] Based on the preparation process of the porous silicon negative electrode material 17 , the porous silicon negative electrode materials 22 and 23 are obtained by adjusting the amount of asphalt.

[0172] Based on the above-mentioned preparation process of the porous silicon negative electrode material 17 , the porous silicon negative electrode material 24 is obtained by adjusting the amount of carbon nanotubes.

[0173] Preparation process of porous silicon negative electrode material 25

[0174] The only difference from the preparation process of the porous silicon negative electrode material 17 is that MgCl2 is used to replace TiO2.

[0175] Preparation process of porous silicon negative electrode material 26

[0176] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon oxide, wherein the deposition temperature is controlled to be 800°C, silicon oxide particles are dispersed in water, and then polyvinyl pyrrolidone (with a molar ratio of 10:1 to silicon dioxide) is added, heated to boiling reflux for 3 hours, and then a sodium hydroxide solution with a concentration of 0.05 mmol / L is added after cooling to room temperature, and then stirred and etched for several hours. The obtained suspension is centrifuged, washed with water 2-3 times, dried at 105°C for 2 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain porous silicon oxide as a core structure;

[0177] 2. Amorphous carbon: The asphalt and the core structure are mixed at a mass ratio of 1.2:1 and then subjected to high temperature treatment for 6 hours at a temperature controlled at 1100°C to obtain a coating layer containing amorphous carbon;

[0178] 3. The material obtained in step 2 is mixed with lithium carbonate at a mass ratio of 1:1.2, and treated at 800°C for 3 hours. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate is formed inside the amorphous carbon and coated on the core structure;

[0179] 4. Finally, the material obtained in step 3 is mixed with the solution of carbon nanotubes, wherein the mass ratio of the material obtained in step 3 to the carbon nanotubes is 1:0.08, and a bonding reaction occurs at a high temperature of 250°C to coat the carbon nanotubes on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0180] Preparation process of silicon negative electrode material 27

[0181] 1. Silicon grains and silicon dioxide are prepared and synthesized by vapor deposition to obtain silicon dioxide as a core structure;

[0182] 2. Amorphous carbon: The asphalt and the core structure are mixed at a mass ratio of 1.2:1 and then subjected to high temperature treatment for 6 hours at a temperature controlled at 1100°C to obtain a coating layer containing amorphous carbon;

[0183] 3. The material obtained in step 2 is mixed with lithium carbonate at a mass ratio of 1:1.2, and treated at 800°C for 3 hours. The lithium ions will pass through the amorphous carbon coating layer, and a first coating layer containing lithium silicate is formed inside the amorphous carbon and coated on the core structure;

[0184] 4. Finally, the material obtained in step 3 is mixed with the solution of carbon nanotubes, wherein the mass ratio of the material obtained in step 3 to the carbon nanotubes is 1:0.08, and a bonding reaction occurs under high temperature treatment at 250°C to coat the carbon nanotubes on the surface of the material to form a third coating layer of amorphous carbon material and carbon nanotubes.

[0185] Tests of the prepared porous silicon negative electrode material:

[0186] Dv50: Refer to the standard GB / T 19077.1-2016 and measure with a laser particle size analyzer (such as Malvern MasterSize 3000). Dv50 is the particle size corresponding to the cumulative volume distribution percentage of the measured material reaching 50%; when the core structure is formed, the Dv50 of silicon element is measured by the above method; after all coating layers are coated, the Dv50 of porous silicon negative electrode material is measured by the above method.

[0187] BET specific surface area: The specific surface area of ​​porous silicon negative electrode materials was determined using the low-temperature nitrogen adsorption-desorption method.

[0188] Determination of the mass content of Li2SiO3: The corresponding Li2SiO3 content is obtained through TOF-SIMES testing, and the standard curve is tested through standard samples. By comparing with the standard curve, the accurate Li2SiO3 content is obtained.

[0189] Determination of the thickness of each coating layer: TOF-SIMES is used to test from the outside to the inside of the particle, and the thickness of each coating layer is determined by the material at different depths.

[0190] Determination of carbon nanotube content: SEM can be used to count the number and length of carbon nanotubes on the surface of multiple silicon particles, and the mass of a single carbon nanotube can be obtained by simulating the chain length and number of molecules of the carbon nanotube. The average value is calculated by calculating the number of multiple carbon tubes as the mass of carbon nanotubes on the surface of porous silicon negative electrode material. Then, the mass percentage of carbon nanotubes C1 and C2 of the porous silicon negative electrode material in the two film layers of the following negative electrode sheet can be calculated by the volume and true density of the porous silicon negative electrode material.

[0191] The test results are recorded in Table 1 and Table 2.

[0192]

[0193]

[0194] 2. Preparation of negative electrode

[0195] Negative electrode 1:

[0196] Coating weight 10mg / cm2 The coating weight ratio of the first coating layer and the second coating layer is 70:30; in the first coating layer, the mass contents of porous silicon negative electrode material 1, graphite, binder, dispersant, conductive agent SP, and conductive agent CNT are 10%, 85.73%, 2%, 1.2%, 1%, and 0.07%, respectively; in the second coating layer, the mass contents of porous silicon negative electrode material 1, graphite, binder, dispersant, conductive agent SP, and conductive agent CNT are 30%, 65.19%, 2.4%, 1.2%, 1%, and 0.21%, respectively.

[0197] The raw materials of the first coating layer are fully stirred and mixed in an appropriate amount of solvent water according to the above weight ratio to form a uniform negative electrode slurry to obtain a first negative electrode slurry; the second negative electrode slurry can be obtained by the same method; the first negative electrode slurry is coated on the surface of the negative electrode collector copper foil, and the second negative electrode slurry is coated on the surface of the first negative electrode slurry; after drying and cold pressing, a negative electrode sheet 1 is obtained, and the surface density M1 of the first film layer and the surface density M2 of the second film layer formed in each negative electrode sheet are recorded in Table 2.

[0198] The difference between the negative electrode sheets 2 to 27 and the negative electrode sheet 1 is that the porous silicon negative electrode material 1 in the negative electrode sheet 1 is replaced by the corresponding porous silicon negative electrode materials 2 to 27 in sequence.

[0199] Negative electrode plates 27 to 36 all use porous silicon negative electrode material 1, but its usage, surface density, thickness, and film layer mass percentage in the first film layer and the second film layer are shown in Table 3. Due to the change in usage, the usage of graphite is adjusted so that the total mass fraction of porous silicon negative electrode material 1, graphite, binder, dispersant and conductive agent SP in the first film layer meets 100%, and the usage of graphite is adjusted so that the total mass fraction of porous silicon negative electrode material 1, graphite, binder, dispersant, conductive agent SP, and conductive agent CNT in the second film layer meets 100%.

[0200] The negative electrode plate 37 uses the silicon negative electrode material 27 to replace the porous silicon negative electrode material 1 in the negative electrode plate 1 .

[0201] Negative electrode test:

[0202] Determination of the porosity of the negative electrode film layer: Take a photo of the CP section, scan it with imaging software, calculate the porosity of the corresponding section, then scan and photograph multiple CP sections, and calculate with software to obtain the porosity of the negative electrode film layer.

[0203] Thickness: The thickness was measured by photographing the CP section.

[0204] The weight ratio of the first film layer to the second film layer is denoted as A.

[0205] Calculate the amount of raw materials used and the data in Tables 1 and 2 per 1cm 2In the first film layer and the second film layer, the masses of the porous silicon negative electrode material in the first film layer and the second film layer are m1 and m2; the mass percentages of the carbon nanotubes belonging to the porous silicon negative electrode material in the first film layer and the second film layer are C1 and C2, excluding the carbon nanotubes in the porous silicon negative electrode material, the masses of the remaining carbon nanotubes in the first film layer and the second film layer are S1 and S2 respectively.

[0206]

[0207] Note: The silicon-based negative electrode materials in the negative electrode plate 37 are all silicon-based negative electrode materials 27.

[0208] 3. Secondary battery

[0209] Example 1

[0210] Negative electrode:

[0211] The above-mentioned negative electrode plate 1 is used as the negative electrode plate of the secondary battery of Example 1.

[0212] Positive electrode:

[0213] Coating weight 25.5mg / cm 2 , the cathode is a single-layer coating, and the mass contents of the ternary materials NCM811, PVDF, conductive agent SP, and conductive agent CNT are 96.5%, 1.5%, 1.5%, and 0.5% respectively;

[0214] The raw materials are fully stirred and mixed in a proper amount of solvent NMP according to the above weight ratio to form a uniform positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode current collector aluminum foil; after drying and cold pressing, a positive electrode sheet is obtained.

[0215] Electrolyte: The electrolyte includes solvent, lithium salt and additives, wherein the types and contents of the solvent are as follows: EC:DMC:DEC=0.3:0.5:0.2, the content of the lithium salt is 1.0 mol / L, and the film-forming additive includes 8% FEC.

[0216] Diaphragm: PE diaphragm;

[0217] The negative electrode sheets of the secondary batteries of Examples 2 to 37 are negative electrode sheets 2 to 37 respectively, and the positive electrode sheets, electrolytes and separators are the same as those of Example 1.

[0218] The negative electrode plate of the secondary battery of Comparative Example 1 is negative electrode plate 38 , and the positive electrode plate, electrolyte and separator are the same as those of Example 1.

[0219] Gram Capacity Test:

[0220] The negative electrode plate and lithium plate were made into a button-type half-cell for testing, and the charge and discharge test was carried out at 25°C at a rate of 0.04C, with a voltage range of 0.05V-2V. The capacity was tested and the gram capacity of the negative electrode was calculated, gram capacity = test capacity / mass of active material.

[0221] Cycle performance test:

[0222] At 25°C, the secondary batteries prepared in the embodiments and comparative examples were charged at a constant current of 1C to a charge cut-off voltage of 4.25V, then charged at a constant voltage to a current of ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a discharge cut-off voltage of 2.8V, left to stand for 5 minutes. This is a charge and discharge cycle. The battery was subjected to a cyclic charge and discharge test according to this method until the battery capacity decayed to 80%. The number of cycles at this time is the cycle life of the battery at 25°C.

[0223] Charging capacity test:

[0224] At 25°C, the batteries of the above embodiments and comparative examples were charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour), specifically including: charging the battery at a constant current of 1C to a voltage of 4.25V, then charging at a constant voltage to a current of ≤0.05C, standing for 5 minutes, and then discharging at a constant current of 0.33C to a voltage of 2.8V, and recording its actual capacity as C0.

[0225] Then the battery is charged with 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, constant current to the full battery charge cut-off voltage of 4.25V or 0V negative electrode cut-off potential (whichever is reached first). After each charge, it is necessary to discharge with 1C0 to the full battery discharge cut-off voltage of 2.8V. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80% The charge rate-negative electrode potential curve under different SOC states is drawn, and the charge rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charge rate is the charging window under the SOC state, which is recorded as C10%SOC, C20%SOC, C30%SOC, C40%SOC, C50%SOC, C60%SOC, C70%SOC, and C80%SOC respectively. The charging time T of the battery from 10%SOC to 80%SOC is calculated according to the formula (60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%, in min. The shorter the time, the better the fast charging performance of the battery.

[0226] The test results are recorded in Table 3.

[0227] Table 3

[0228]

[0229]

[0230] According to the comparison of Examples 1 to 5, it can be seen that the D V 50 changes will directly affect the cycle performance and charging capacity of the battery, especially as the D V As the value increases by 50, the charging capacity of the battery decreases.

[0231] According to the comparison of Examples 6 to 10, it can be seen that the D V 50 changes will affect the battery's charging capacity and cycle performance. V With an increase of 50, the cycle performance and charging capacity of the battery both decrease.

[0232] According to the comparison of Examples 11 to 14, it can be seen that the change in the thickness of the first coating layer containing lithium silicate will affect the charging capacity and cycle performance of the battery. As the thickness of the first coating layer increases, the cycle performance of the battery improves, but the charging capacity increases.

[0233] According to the comparison of Examples 17 to 20, it can be seen that the change in the thickness of the metal compound of the second coating layer silicon will affect the charging capacity and cycle performance of the battery. As the thickness of the second coating layer increases, the cycle performance of the battery first increases and then decreases, and the charging capacity gradually decreases. This is because the second coating layer increases the anti-expansion ability of the silicon material and improves the cycle performance. However, the conductivity of the second coating layer is poor, and the increase in coating thickness will deteriorate the dynamics.

[0234] According to the comparison of Examples 1, 17 and 27, it can be seen that different coating methods have a significant impact on the cycle performance and charging capacity of the battery.

[0235] According to the comparison between Example 1, Examples 28 to 37 and Comparative Example 1, the increase in the content of porous silicon negative electrode material in the second film layer helps to improve the charging capacity of the battery; and the gram capacity of Example 28 is more prominent because the content of porous silicon negative electrode in the first film layer is relatively high, and its cycle performance is also reduced because the content of porous silicon negative electrode in the first film layer is relatively high.

[0236] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A negative electrode sheet, comprising a current collector (01) and a negative electrode film layer, wherein the negative electrode film layer comprises: A first film layer (02) is arranged on one side or both sides of the current collector (01); A second film layer (03) is arranged on a side of the first film layer (02) away from the current collector (01); The negative electrode active material of the first film layer (02) and the negative electrode active material in the second film layer (03) each independently include a silicon-based negative electrode material, and the silicon-based negative electrode material in the second film layer (03) includes a porous silicon negative electrode material (10), and the content of the silicon-based negative electrode material in the first film layer (02) is less than the content of the silicon-based negative electrode material in the second film layer (03).

2. The negative electrode sheet according to claim 1, wherein: The surface density M1 of the first film layer (02) is in the range of 4.5 mg / cm 2 ~20mg / cm 2 The surface density M2 of the second film layer (03) is in the range of 4.5 mg / cm 2 ~20mg / cm 2 ; Optionally, the weight ratio of the first film layer (02) and the second film layer (03) is 95:5 to 30:70, and can be further optionally 90:10 to 40:60; Optionally, the porosity of the first film layer (02) is in the range of 20% to 50%, the porosity of the second film layer (03) is in the range of 20% to 70%, and the porosity of the negative electrode film layer is in the range of 20% to 70%; Optionally, the thickness of the second film layer (03) is 10μm to 20μm.

3. The negative electrode sheet according to claim 1 or 2, wherein: The mass content of the silicon-based negative electrode material in the first film layer (02) is 0.5% to 50%; and / or the mass content of the porous silicon negative electrode material (10) in the second film layer (03) is 0.5% to 70%; optionally, the mass content of the porous silicon negative electrode material (10) in the negative electrode film layer is 1% to 60%.

4. The negative electrode sheet according to any one of claims 1 to 3, wherein: The second film layer (03) comprises the porous silicon negative electrode material (10), a graphite negative electrode material, a binder, a dispersant and a conductive agent, wherein the conductive agent comprises one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of the porous silicon negative electrode material (10) in the second film layer (03) is 0.5% to 70%; optionally, the mass percentage of the graphite negative electrode material in the second film layer (03) is 25% to 90%; optionally, the mass percentage of the binder in the second film layer (03) is 1% to 8%; optionally, the mass percentage of the dispersant in the second film layer (03) is 0.5% to 2%; optionally, the mass percentage of the conductive carbon in the second film layer (03) is 0.5% to 5%; optionally, the mass percentage of the carbon nanotubes in the second film layer (03) is 0.05% to 2%.

5. The negative electrode sheet according to any one of claims 1 to 4, wherein: The first film layer (02) comprises the silicon-based negative electrode material, the graphite negative electrode material, the binder, the dispersant and the conductive agent, wherein the conductive agent comprises one or more of conductive carbon and carbon nanotubes; optionally, the mass percentage of the silicon-based negative electrode material in the first film layer (02) is 0.5% to 50%; optionally, the mass percentage of the graphite negative electrode material in the first film layer (02) is 45% to 97.5%; optionally, the mass percentage of the binder in the first film layer (02) is 1% to 3%; optionally, the mass percentage of the dispersant in the first film layer (02) is 1% to 3%. 02) has a mass percentage of 0.3% to 1.5%; optionally, the mass percentage of the conductive carbon in the first film layer (02) is 0 to 3%; optionally, the mass percentage of the carbon nanotubes in the first film layer (02) is 0 to 0.5%; optionally, the silicon-based negative electrode material includes any one or more of the group consisting of silicon material, silicon oxide material and porous silicon negative electrode material (10), and the content of the porous silicon negative electrode material (10) in the first film layer (02) is less than the content of the porous silicon negative electrode material (10) in the second film layer (03).

6. The negative electrode sheet according to any one of claims 1 to 5, wherein: The Dv of the porous silicon negative electrode material (10) 50 The BET specific surface area of ​​the porous silicon negative electrode material (10) is between 1 m 2 / g~30m 2 / g; optionally between 6m 2 / g~20m 2 / g.

7. The negative electrode sheet according to any one of claims 1 to 6, wherein: The porous silicon negative electrode material (10) comprises: A core (11), wherein the core (11) is porous silicon, and the porous silicon includes silicon and silicon compounds, and the silicon compounds include silicon oxides; A coating layer is coated on the surface of the core (11).

8. The negative electrode sheet according to claim 7, wherein: The coating layer includes any one or more of metal compounds of silicon, lithium silicate, amorphous carbon, and carbon nanotubes.

9. The negative electrode sheet according to claim 8, wherein: The coating layer comprises: A first coating layer (12), the first coating layer (12) is coated on the surface of the core (11), and the first coating layer (12) comprises lithium silicate; A second coating layer (13), the second coating layer (13) is coated on the surface of the first coating layer (12), the second coating layer (13) comprises a metal compound of silicon, and optionally the metal element of the metal compound of silicon comprises Ti, Mg and / or Al; A third coating layer (14), the third coating layer (14) is coated on the surface of the second coating layer (13), the third coating layer (14) comprises amorphous carbon, and optionally, the material of the amorphous carbon comprises hard carbon and / or soft carbon.

10. The negative electrode sheet according to claim 8, wherein: The coating layer comprises: A first coating layer (12), the first coating layer (12) is coated on the surface of the core (11), and the first coating layer comprises the lithium silicate; A third coating layer (14), the third coating layer (14) is coated on the surface of the first coating layer (12), the third coating layer (14) comprises the amorphous carbon, and optionally, the material of the amorphous carbon comprises hard carbon and / or soft carbon.

11. The negative electrode sheet according to any one of claims 7 to 8 and 10, wherein: The silicon compound further includes a silicon metal compound, and the silicon metal compound is coated on the surface of the silicon element. Optionally, the metal element of the silicon metal compound includes Ti, Mg and / or Al.

12. The negative electrode sheet according to any one of claims 9 to 11, wherein: The third coating layer also includes the carbon nanotubes.

13. The negative electrode sheet according to claim 12, wherein: The masses of the porous silicon negative electrode material (10) in the first film layer (02) and the second film layer (03) are m1 and m2 respectively; the mass percentages of the carbon nanotubes belonging to the porous silicon negative electrode material (10) in the first film layer (02) and the second film layer (03) are C1 and C2 respectively; Excluding the carbon nanotubes in the porous silicon negative electrode material (10), the masses of the remaining carbon nanotubes in the first film layer (02) and the second film layer (03) are S1 and S2 respectively, the first film layer (02) and the second film layer (03) are the first film layer (02) and the second film layer (03) per unit area respectively, and the following relationship is satisfied: (m2×C2+S2) / M2=(m1×C1+S1) / M1, m2≥m1, S1≥S2, S2=m1×m2×(C2-C1) / (m2-m1).

14. The negative electrode sheet according to any one of claims 7 to 13, wherein: The Dv50 range of the silicon single substance is: 0<Dv50≤10nm; optionally, the Dv50 range of the silicon single substance is: 2nm<Dv50≤8nm.

15. The negative electrode sheet according to any one of claims 7 to 14, wherein: The chemical formula of the silicon oxide is SiOx, wherein 0<x≤2; the Dv50 range of the silicon oxide is: 2μm≤Dv50≤13μm.

16. The negative electrode sheet according to claim 9 or 10, wherein: The lithium silicate includes one or more of Li2SiO3, Li2Si2O5, Li4SiO4, Li2Si3O7, Li8SiO6, Li6Si2O7, Li4Si2O7, Li2Si4O7 and LiSiO3; optionally, the lithium silicate includes at least Li2SiO3, and further optionally, the mass of the Li2SiO3 is at least 50% of the mass of the first coating layer, and more optionally, the mass of the Li2SiO3 is at least 70% of the mass of the first coating layer.

17. The negative electrode sheet according to any one of claims 9 to 16, wherein: The thickness of the first coating layer is 10% to 80% of the particle radius of the porous silicon negative electrode material (10). Optionally, the thickness of the second coating layer is 1nm to 50nm. Optionally, the thickness of the third coating layer is 1nm to 1000nm, and can be 5nm to 300nm.

18. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein: The negative electrode plate is the negative electrode plate according to any one of claims 1 to 17.

19. An electrical device comprising a secondary battery, wherein: The secondary battery is selected from the secondary battery according to claim 18.

Citation Information

Patent Citations

  • Negative pole piece, electrochemical device and electronic device

    CN111261834A

  • Silicon-based negative electrode material and preparation method and application thereof

    CN112186188A

  • Secondary battery and fabrication method therefor, and apparatus containing secondary battery

    CN113875049A

  • Negative plate and lithium ion battery comprising same

    CN114050234A

  • Secondary battery and fabrication method therefor, and apparatus containing secondary battery

    WO2021217639A1

Cited By

  • Negative pole piece, preparation method thereof and battery

    CN119812214A

  • Negative plate, secondary battery, battery pack and electric equipment

    CN121790289A